Mastering facilitation : a guide for assisting teams and achieving great outcomes - Jones, Morgan (Routledge, 2021)
"With business and organizations moving at an ever -faster pace and facing evermore more and more demanding challenges, the need for efficient, succinct and productive interaction between individuals of those businesses and organizations is more important than ever. With the bounds of communication restrictions abandoned through technological advances (we can now see and hear anyone across any manner of virtual platforms anywhere around the globe) and with a greater understanding of the underlying dynamics of human interaction, unprecedented pressure has been thrust upon the individual or individuals whom, often, enable these dynamic interactions: the facilitator. Many of us have, at one time or other, been responsible for a meeting - whether between a small number of individuals or an entire organization of hundreds, or possibly thousands, of business men and women. Or, perhaps, we've had to be the mediator in a family dispute closer to home, or managed a discussion between two, feuding friends or colleagues. One way or another, chances are, all of us has have been a facilitator at some point in our lives. With the ever-growing demands placed on facilitators, this book delivers methodical, structured approach to facilitation. This book is the definitive guide to instruct and assist facilitators - both new and experienced - with a set of guidelines and underlying theory that will benefit any facilitator, whether as a mediator between two individuals, single-handedly facilitating a group of one hundred, or working as part of a facilitation team in a multinational corporation. The first part of the book, develops the core basic skills of those new to the art of facilitating. There are many examples and exercises to show the reader how to apply them in different situations. The second part of the book is for more experienced facilitators as it focuses on more advanced skills and tackling difficult situations. Specific tools and techniques are illustrated for the reader. Essentially, this book is aimed at developing and mastering the art of facilitation. Facilitation is the art of getting the best out of groups of people to brainstorm solve problems and gain consensus. Based on 30 years' experience of the author and running, multiple facilitation training courses across the globe, it is aimed at upskilling people, managers and leaders to drive change and consensus with groups through running workshops and meetings"--